Analisis Skor Reflux Symptom Index (RSI) pada Pasien Laryngopharyngeal Reflux dengan Pemberian Lansoprazol dan Ranitidin di RSUP Dr M Djamil Padang - Muhammad Rofid Adha; Ade Asyari; Asrawati Asrawati; Elly Usman; Syandrez Prima Putra (Fakultas Kedokteran Universitas Andalas, 2024)
Laryngopharyngeal reflux (LPR) is a condition caused by the movement of stomach acid back into the pharynx, larynx and upper digestive tract. One of the diagnostic tools that can be used in LPR is the Reflux Symptom Index (RSI), where RSI can also be used to evaluate symptom improvement in patients before and after administering drug therapy. This study aims to determine the average RSI score before and after giving therapy to LPR patients at Dr M Djamil Hospital, Padang. This research is a retrospective analytical study by taking medical record data on LPR patients at Dr M Djamil Hospital Padang using consecutive sampling techniques. Data analysis was carried out univariately to determine the frequency distribution and bivariately using the paired T-test to analyze the average RSI score. The results of this study were that the majority of LPR sufferers were >50 years old (52.9%), the majority gender was female (76.2%), and the most common complaints were a lump in the throat (100%) and heartburn (100%). The average RSI score before giving therapy was found to be 22.12 ± 6.827 and after giving therapy was 13.18 ± 7.844. Based on the data analysis carried out, the p<0.001. The conclusion of this study was that there was a significant change in the average RSI value before and after administration of lansoprazole and ranitidine therapy in LPR patients.